The Shift from Affix to Clitic in the History of the English Genitive: Evidence from John of Trevisa’s Polychronicon - Rodrigo Pérez Lorido (SELIM, 2025)
In this article I address the question of the change in grammatical nature for the English genitive from inflectional affix to clitic. I focus on the rise of the group genitive, a construction in which the mark for possession is not attached to the head of a possessor phrase but to the rightmost element of it—as in the king of England’s name—and the role the his genitive or separated genitive played in the whole process. In my argumentation I present prima facie evidence derived from the analysis of one of the first texts in the history of English where the presence of the group genitive is most noticeable while consistently using the his genitive: John of Trevisa’s translation of Ranulph Higden’s Polychronicon (dated around 1387). The results suggest that the his genitive may have played a major role in the rise of the group genitive in English, challenging Allen’s (1997, 2003, 2008) hypothesis that the group genitive developed after the generalisation of the inflectional genitive ending -(e)s to all noun classes as well as Janda’s (1980, 1981) theory that the old inflectional genitive was reanalysed as a clitic as a result of deflexion.